Prevention is the key - a multidimensional model for social well-being of the elderly - Almassy, Zsuzsanna; Szemán-Nagy, Anita; Farkas, Réka; Csinády, Adriána (Magyar Gerontológia, 2022)
Our research group identified a huge need for research on social well-being in the elderly population. In Hungary so far not much has been published in this topic, however, understanding the key elements of well-being is a growing area of research in gerontology all around the world, since it is crucial how we manage our lives in old age.